BURN WOUND HEALING ACTIVITY OF ETHANOL EXTRACT OF ECENG GONDOK (Eichornia crassipes) LEAVES - Juwita Ramadhani; Aris Fadillah; Hasniah Hasniah; Karina Erlianti (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2024)
Eceng gondok is a weed plant that lives in shallow water areas. The aim of this research was to determine the burn wound healing activity of an ethanol extract of Eceng gondok leaves. The study utilized 28 male mice with burn injuries as test animals, dividing them into 4 groups. We gave a gel containing an ethanol extract to the 10% group. The 0% group received a gel base; the positive control group received Bioplacenton® gel; and the negative control group received no treatment. For 14 days, we administered treatment to all treatment and control groups once a day and measured the burn wound's diameter using the Morton method every two days. Data shown were significant differences between the 10% extract group and the positive control groups. The concentration that is effective in burn wound healing is 10%, with the smallest wound diameter and the largest healing percentage.